2018
DOI: 10.1093/mnras/sty058
|View full text |Cite
|
Sign up to set email alerts
|

New cataclysmic variables and other exotic binaries in the globular cluster 47 Tucanae*

Abstract: We present 22 new (+3 confirmed) cataclysmic variables (CVs) in the non corecollapsed globular cluster 47 Tucanae (47 Tuc). The total number of CVs in the cluster is now 43, the largest sample in any globular cluster so far. For the identifications we used near-ultraviolet (NUV) and optical images from the Hubble Space Telescope, in combination with X-ray results from the Chandra X-ray Observatory. This allowed us to build the deepest NUV CV luminosity function of the cluster to date. We found that the CVs in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 96 publications
8
29
0
Order By: Relevance
“…This brings then that the CV masses are dominantly the WD masses. Rivera Sandoval et al (2018) inferred CV masses of 1.4 ± 0.2 M ⊙ for both bright and faint CVs in 47 Tuc, which is similar to what has been found for bright CVs in NGC 6397 and NGC 6752. However, this implies that, for the faint CVs, the inferred WD masses in 47 Tuc are ∼ 1.2 M ⊙ , which is much higher than the standard WD mass in CVs.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This brings then that the CV masses are dominantly the WD masses. Rivera Sandoval et al (2018) inferred CV masses of 1.4 ± 0.2 M ⊙ for both bright and faint CVs in 47 Tuc, which is similar to what has been found for bright CVs in NGC 6397 and NGC 6752. However, this implies that, for the faint CVs, the inferred WD masses in 47 Tuc are ∼ 1.2 M ⊙ , which is much higher than the standard WD mass in CVs.…”
supporting
confidence: 81%
“…In other words, hereafter we only investigate properties of present-day CVs that are likely to be observed via multiple technique methods, since these are the most important ones and can potentially lead to some constraints. So far we know that core-collapsed GCs show 2 populations of CVs (Cohn et al 2010;Lugger et al 2017), and that based on that we can separate the CV population for non-core-collapsed GCs (Cool et al 2013;Rivera Sandoval et al 2018). In order to investigate whether we can reproduce some observational features of these two populations, we first select the detectable CVs in our models 4 .…”
Section: Present-day CV Populationmentioning
confidence: 99%
“…2) the UV or blue excesses that originate from the hot accretion disc and/or WD surface in typical CVs. Marked optical/UV variabilities are common in some CVs, which might alter UV flux by up to 1 magnitude on timescales of hours (see e.g., Rivera Sandoval et al 2018), but cannot be responsible for the strong red excesses of U18 observed in all 3 CMDs. Considering the radio and UV/optical data, we rule out a CV interpretation for U18.…”
Section: U18: a Hidden Msp?mentioning
confidence: 99%
“…Signs of optical/UV variability can be helpful to further confirm the nature of the source, especially for CV identifications, since most CVs appear as blue variable stars (see e.g. Cool et al 1998;Edmonds et al 2003b;Dieball et al 2017;Rivera Sandoval et al 2018).…”
Section: Optical Variabilitymentioning
confidence: 99%
“…High angular resolution X-ray observations with Chandra have revealed large numbers of faint (L X ∼ 10 29−34 erg s −1 ) X-ray sources in globular clusters (Verbunt & Lewin 2006;Heinke et al 2010). The faint X-ray population is composed of multiple source classes, including: quiescent low-mass Xray binaries (qLMXBs) in which accretion onto the NS is thought to be stopped or at least largely suppressed (Campana et al 1998;Rutledge et al 2002;Heinke et al 2003;Chakrabarty et al 2014) with luminosities typically ∼ 10 4 times fainter than during outbursts; cataclysmic variables (CVs) where white dwarfs accrete from low-mass companions (Hertz & Grindlay 1983;Cool et al 1995;Pooley et al 2002;Cohn et al 2010;Rivera Sandoval et al 2018); millisecond pulsars (MSPs), thought to be radio pulsars that have been spun up by accretion (Bhattacharya & van den Heuvel 1991), which are observed in both X-ray (Saito et al 1997;Bogdanov et al 2006) and radio (Ransom et al 2005;Freire et al 2017); and chromospherically active binaries (ABs) composed of two tidally-locked non-degenerate stars, wherein fast rotation induces active coronal regions that emit (relatively faint, L X < 10 31 erg s −1 ) X-rays (Bailyn et al 1990;Dempsey et al 1993;Grindlay et al 2001;Heinke et al 2005b). The qLMXBs and CVs appear to be correlated with encounter rate (Pooley et al 2003;Heinke et al 2003;Pooley & Hut 2006;Bahramian et al 2013), while the ABs are expected to be primordial in origin (Bassa et al 2004;Verbunt et al 2008;Bassa et al 2008;Lu et al 2009;Huang et al 2010).…”
Section: Introductionmentioning
confidence: 99%